Star Carr Studies in Technology, Subsistence and Environment - Milner, Nicky (Star Carr, 2018)
Star Carr is one of the most important Mesolithic sites in Europe. It was discovered in the late 1940s by John Moore and then excavated by Grahame Clark from 1949-1951, becoming famous in the archaeological world for the wealth of rare organic remains uncovered including barbed antler points and antler headdresses. However, since the original excavations there has been much debate about how the site was used: was it a residential base camp, a hunting camp or even a ritual site? From 2003-2015, excavations directed by Conneller, Milner and Taylor aimed to answer these questions. This work has demonstrated that the site is much larger and more complex than ever imagined and was in use for around 800 years. The excavations show that Mesolithic groups were highly invested in this place: there is evidence for a number of structures on the dryland (the oldest evidence for 'houses' in Britain), three large wooden platforms along the edge of the lake, and the deposition of rare artefacts into the lake edge, including more antler headdresses and a unique, engraved shale pendant. People continued to occupy the site despite changes in climate over this period. The main results of our work are contained in two volumes: the first provides an interpretation of the site, and the second provides detail on specific areas of research. The main results of our work are contained in two volumes: the first volume provides an interpretation of the site, and the second volume provides detail on specific areas of research.